Why the single market remains the EU's core business. Issue 5 (2nd September 2016) - Pelkmans, Jacques
Abstract: This paper examines the centrality of the single market to the EU. Its main conclusion is that the single market will remain central to the Union in future and that although it is not immune to crises, because it is the Union's hard core and has powerful governance, serious erosion is unlikely. The paper examines the centrality of the single market by analysing in-depth the functional logic of market integration and the progress and deficits that characterise the Union's market regime. The paper then explores the meaning of the internal market for EMU and argues that the single market is the 'E' in EMU. The issue of the euro 'ins' and 'outs' is addressed. The paper ends by asking if the single market is resilient against crises and concludes in the affirmative.